Tìm x, biết :
x+18=6-2x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(2x-6)(2x-18)=0
\(\Rightarrow\hept{\begin{cases}2x-6=0\\2x-18=0\end{cases}}\Rightarrow\hept{\begin{cases}2x=6\\2x=18\end{cases}}\Rightarrow\hept{\begin{cases}x=3\\x=9\end{cases}}\)
Vậy ...
Ta có 4( 18 - 5x ) - 12( 3x - 7 ) = 15( 2x - 16 ) - 6( x + 14 )
⇔ 4.18 - 4.5x - 12.3x - 12.( - 7 ) = 15.2x - 15.16 - 6.x - 6.14
⇔ 72 - 20x - 36x + 84 = 30x - 240 - 6x - 84
⇔ 156 - 56x = 24x - 324 ⇔ 56x + 24x = 156 + 324
⇔ 80x = 480 ⇔ x = 6.
Vậy giá trị x cần tìm là x = 6.
Ta có 4( 18 - 5x ) - 12( 3x - 7 ) = 15( 2x - 16 ) - 6( x + 14 )
⇔ 4.18 - 4.5x - 12.3x - 12.( - 7 ) = 15.2x - 15.16 - 6.x - 6.14
⇔ 156 - 56x = 24x - 324 ⇔ 56x + 24x = 156 + 324
⇔ 80x = 480 ⇔ x = 6.
Vậy giá trị x cần tìm là x = 6.
a)2x - 12 = 18
2x=18+12
2x=30
x=30:2
x=15
b)6^2 - (x+3)=45
36-(x+3)=45
x+3=36-45
x+3=-9
x=-9-3
x=-12
a, (2\(x\) -5) + 17 = 6
2\(x\) - 5 = 6 - 17
2\(x\) - 5 = - 11
2\(x\) = - 11 + 5
2\(x\) = -6
\(x\) = -3
b, (-18).\(x\) = - 36
\(x\) = -36 : (-18)
\(x\) = 2
c, 15 - (-11\(x\) - 7) = -22
- 11\(x\) - 7 = 15 + 22
-11\(x\) - 7 = 37
11\(x\) = -37 - 7
11\(x\) = - 44
\(x\) = - 4
a) \(\left(2x-5\right)+17=6\Rightarrow2x-5=-11\Rightarrow2x=-6\Rightarrow x=-3\)
b) \(\left(-18\right)x=-36\Rightarrow x=\left(-36\right):\left(-18\right)=2\)
c) \(15-\left(-11x-7\right)=-22\)
\(\Rightarrow15+11x+7=-22\)
\(\Rightarrow11x=-22-7-15\)
\(\Rightarrow11x=-44\)
\(\Rightarrow x=-44:11=-4\)
a: 18:(x-3)=6
=>x-3=18:6=3
=>x=3+3=6
b: \(3^{x-1}+4=85\)
=>\(3^{x-1}=81\)
=>\(3^{x-1}=3^4\)
=>x-1=4
=>x=5
c: 2x+3x=55
=>5x=55
=>x=55/5=11
d: \(\left(x-3\right)^3+11=53\)
=>\(\left(x-3\right)^3=53-11=42\)
=>\(x-3=\sqrt[3]{42}\)
=>\(x=\sqrt[3]{42}+3\)
a) 18 : (x - 3) = 6
x - 3 = 18 : 6
x - 3 = 3
x = 3 + 3
x = 6
b) 3ˣ⁻¹ + 4 = 85
3ˣ⁻¹ = 85 - 4
3ˣ⁻¹ = 81
3ˣ⁻¹ = 3⁴
x - 1 = 4
x = 4 + 1
x = 5
c) 2x + 3x = 55
5x = 55
x = 55 : 5
x = 11
d) Sửa đề:
(x - 3)³ - 11 = 53
(x - 3)³ = 53 + 11
(x - 3)³ = 64
(x - 3)³ = 4³
x - 3 = 4
x = 4 + 3
x = 7
x + 18 = 6 - 2x
x + 2x = 6 - 18
3x = - 12
x = -4
=.= hk tốt!!
x+2x = 6 - 18
3x = -12
x = -12 : 3
x = -4
Vậy......